Family Flexibility and its Relationship to Mental Health among Gifted Students in King Abdullah II School of Excellence in Aqaba Governorate - Aseel Alzawayiduh; Moneera Almsbhieen (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
The study aims to identify the level of family flexibility and its relationship to mental health, and to identify the differences in the level of family flexibility and mental health according to gender differences, among gifted students at King Abdullah II School for Excellence in Aqaba Governorate. The study followed the correlative descriptive approach, where the study sample consisted of 265 students (129 males and 136 females) from King Abdullah II School for Excellence in Aqaba Governorate in Jordan. The two scales of family flexibility (27 items), and mental health (41) items were applied to them. The results showed that the level of family flexibility is high, while the level of mental health was medium, the findings also showed that there is a significant positive correlation at the significance level (0.05) between the scores of family flexibility and mental health, and that there is no significant statistical difference in the scales of family flexibility and mental health due to the gender. The study recommends enhancing the level of family flexibility among the families of talented students by holding meetings between the families to exchange experiences regarding the flexible family environment, and work on developing their mental health by activating the role of school counseling, and conducting further studies deals with the relationship of family resilience with some variables such as: academic achievement, creative self-efficacy.